Menurunnya Rasa Nasionalisme Dikalangan Generasi Muda Diera Digital - Fadhila Hasibuan (CV. PUSDIKRA MITRA JAYA, 2026)
The rapid development of technology and globalization in the digital era have brought about significant changes in the mindsets, behaviors, and lifestyles of Indonesia's young generation. Easy access to global information has led to a greater familiarity with foreign cultures than with national culture, resulting in a decline in nationalism and concern for national values. This study aims to analyze the factors causing the decline in nationalism among the younger generation and to find effective solutions to revitalize it. The research method used is a descriptive qualitative approach with a literature review approach, which examines various literature and data related to the phenomenon of nationalism in the digital era. The results indicate that the main causes of the decline in nationalism are the influence of foreign cultures, excessive use of social media, and weak character education in the family and school environment. Possible efforts include strengthening civic education, instilling the values of Pancasila, and utilizing digital media to revitalize patriotism.